Analisis emisi gas buang kendaraan berbahan bakar etanol - Mara, I.M.; Nuarsa, I.M.; Alit, I.B.; Sayoga, I.M.A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2019)
Exhaust emissions of motorcycles are very harmful to the environment and to human health. Ethanol is an alternative fuel that can be used to substitute gasoline. Ethanol can be obtained from the fermentation of agricultural products that contain carbohydrates. Ethanol is a clean fuel and has high octane number so it produces less harmfull exhaust emission. In this research, a single cylinder four-stroke gasoline engine of Honda Astrea Legenda 100 cc was used to examine the fuel consumption and exhaust emission gas by varying the ignition timing (15o, 20o and 25o) before TDC and engine rotation (1500, 2500, 3500, 4500, and 6000 rpm) at the entire transmission gear (N, 1, 2, 3 , and 4) using ethanol 96% fuel. The results show that there is a reduction in the fuel consumption and exhaust emissions such as CO, HC and increase the levels of CO2 emissions by using ethanol 96% fuel at 20° before TDC ignition timing. Moreover, the lowest fuel consumption value is achieved at the ignition timing 20º before TDC at the engine speed 1500 rpm at transmission gear 4 that is 0.1 kg/h. In addition, the lowest CO emission value is 0.17 % volume at 6000 rpm engine rotation with transmission gear 4, the lowest HC emission value is 57, 67 ppm at 6000 rpm engine rotation with transmission gear 4 and the highest CO2 value is 13.86 % volume at 6000 rpm rotation with transmission gear 4.